Fast and slow myosins as markers of muscle injury. Issue 7 (10th December 2007) - Guerrero, M; Guiu-Comadevall, M; Cadefau, J A; Parra, J; Balius, R; Estruch, A; Rodas, G; Bedini, J L; Cussó, R
Abstract : Objective: The diagnosis of muscular lesions suffered by athletes is usually made by clinical criteria combined with imaging of the lesion (ultrasonography and/or magnetic resonance) and blood tests to detect the presence of non-specific muscle markers. This study was undertaken to evaluate injury to fast and slow-twitch fibres using specific muscle markers for these fibres. Methods: Blood samples were obtained from 51 non-sports people and 38 sportsmen with skeletal muscle injury. Western blood analysis was performed to determine fast and slow myosin and creatine kinase (CK) levels. Skeletal muscle damage was diagnosed by physical examination, ultrasonography and magnetic resonance and biochemical markers. Results: The imaging tests were found to be excellent for detecting and confirming grade II and III lesions. However, grade I lesions were often unconfirmed by these techniques. Grade I lesions have higher levels of fast myosin than slow myosin with a very small increase in CK levels. Grade II and III lesions have high values of both fast and slow myosin. Conclusions: The evaluation of fast and slow myosin in the blood 48 h after the lesion occurs is a useful aid for the detection of type I lesions in particular, since fast myosin is an exclusive skeletal muscle marker. The correct diagnosis of grade I lesions can prevent progression of the injury in athletes undergoing continual training sessions and competitions, thus aiding sports physicians in their decision making.